Reduced Rho-dependent transcription termination permits NusA-independent growth of Escherichia coli. - Zheng, C (1994)
NusA and Rho are essential Escherichia coli proteins that influence transcription elongation and termination. We show that an E. coli derivative unable to express NusA, because its sole nusA gene contains a large deletion/substitution, is viable providing that the bacterium also carries a rho mutation that reduces transcription termination. This Rho-mediated suppression is not allele specific, since either a mutation changing amino acid 134 [rho(E134D)] or a mutation changing amino acid 352 (rho1) allows growth of a nusA-deleted E. coli. However, both rho mutations similarly decrease transcription termination 8- to 9-fold. We propose that the essential role of NusA is to enhance pausing of RNA polymerase at certain sites, permitting tight coupling of transcription and translation. This coupling interferes with Rho access to and/or movement on the nascent RNA and blocks premature termination of transcription. Thus, NusA-dependent coupling should be less important in a mutant with low Rho activity. The fact that E. coli grows without NusA argues that NusA should be considered an accessory factor rather than a subunit of RNA polymerase.